Comparative analysis of eliciting capacity of raw and roasted peanuts: the role of gastrointestinal digestion. (January 2020) - Di Stasio, Luigia; Tranquet, Oliver; Picariello, Gianluca; Ferranti, Pasquale; Morisset, Martine; Denery-Papini, Sandra; Mamone, Gianfranco
Graphical abstract: Highlights: BBM digestion reduces the eliciting properties of roasted peanuts. Roasting does not affect the eliciting properties of undigested peanuts. Roasting affects digestion stability of peanut proteins. Abstract: This study investigated the simultaneous impact of food matrix and processing on the food allergy eliciting capacity of peanuts in a physiologically relevant context. Whole raw and roasted peanuts were subjected to in vitro digestion combining the harmonized oral-gastric-duodenal digestion models with brush border membrane enzymes (BBM) to simulate the jejunal degradation of peptides. SDS-PAGE and HPLC analysis showed that roasting increased digestibility of peanuts and this trend was even more evident after BBM degradation. The eliciting properties of raw and roasted peanuts were assessed by Rat Basophil Leukemia assay in the presence of sera from peanut-allergic patients. As general features, the BBM digestion reduced allergenicity of roasted peanuts compared to the raw counterpart, suggesting that intestinal peptidases effectively contribute to further destroy specific domains of peanut allergens. These findings provide new and more realistic insights in the stability of peanut allergens within their natural matrix.